Two women - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows two women posing together. The woman on the left has her right hand behind her back and her left arm around the second woman with her hand resting on her waist. The woman on the right has her left arm across the body of the first woman with her hand resting on her waist. There are people milling around them.